Atlas of Essential Dermatopathology - Masterpol, Kasia S. (Springer London : Imprint: Springer, 2013)
Dermatopathology often presents considerable difficulty for the dermatologist in training when defining the subtle differences in the appearance of various conditions. This Atlas of Essential Dermatopathology is based on materials developed during dermatopathology teaching signout at the Massachusetts General Hospital and replicates the experience at the microscope. It contains numerous hand drawn sketches and tables plus stunning histological images to describe the appearances of common dermatologic conditions. Each chapter is brief and focuses on the main learning points. Tables of special stains, immunohistochemical markers and a glossary of terms are also included to broaden the readers experience. The content is based on the most frequently encountered processes in the MGH Dermatopathology Unit; it is not intended to be comprehensive but rather an outline and atlas of the essentials in diagnostic dermatopathology. This book will therefore be an indispensable primer for trainees of all levels students and residents alike in dermatology and pathology.